List of Staphylinids of Lagodekhi Reserve with some new records from Sakartvelo (Georgia) - Japoshvili, George; Khachikov, Eduard (Zootaxa, 2020)
The rove beetles (Coleoptera: Staphylinidae) are one of the most diverse families of beetles comprising more than 63650 species worldwide (Irmler et al. 2018). It is the best studied coleopteran family in Georgia (Herman, 2001; Schülke & Smetana, 2015), with more than 750 species recorded (Tarkhnishvili & Chaladze, 2019). The first records of Staphylinidae from Lagodekhi were reported by Zhizhilashvili (1941), who recorded 12 species of rove beetles from the reserve: Anotylus hybridus Eppelsheim, 1878 as Oxytelus; Anotylus gibbulus Eppelsheim, 1878 as Oxytelus; Xantholinus variabilis Hochhuth, 1851; Cordalia obscura Gravenhorst; Philonthus parvicornis Gravenhorst, 1802 as P. agilis Gravenhorst; Stenus circularis Gravenhorst, 1802 as S. clavulus Hochhuth; S. cribratus Kiesenwetter, 1850; Tachyporus hypnorum (Fabricius, 1775); Ocypus nitens (Schrank, 1781) as Staphylinus similis Fabricius; Quedius minor Hochhuth, 1849 as Q. distincticolor Roubal; Aleochara intricata Mannerheim; Olophrum caucasicum Fauvel, 1875. The record of Medon bicolor (Olivier, 1795) (as Sunius) in the same paper is erroneous because the species is absent from Georgia. Coiffait (1969) described Quedius grouziacus as a new species from Lagodekhi, however the species was later synonymized with Q. suramensis Epelsheim, 1880 by Solodovnikov (2002). Ushakov (1988) recorded Gauropterus sanguinipes Reitter, 1889, Gyrohypnus angustatus Stephens,1832 and Atrecus affinis (Paykull, 1789) as Baptolinus affinis caucasius Roubal, 1933. Gusarov and Koval (2002) registered Korgella caucasica (Gusarov & Koval, 2002; Özdikmen, 2005), as Heinzia. Later Shavrin & Khachikov (2019) added Acrolocha amabilis (Heer, 1841) which was new to the staphylinid fauna of Georgia. There have been no other focused studies on the Staphylinidae of Lagodekhi Protected Areas (LPA), though we recognize that there are likely further records in the literature.